Gingival Lipoma: A Rare Case Report - Shrestha, Sweta; Pradhan, Shaili; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Lipomas are benign tumours of mesenchymal origin (mature adipocytes) that are comparatively uncommon in the oral cavity corresponding to less than 4.4% of all benign oral soft tissue tumors. Clinically, they present as slow growing, soft, asymptomatic masses. Histopathologically, they appear as thinly encapsulated lesion composed of mature adipocytes with inconspicuous vascularity. The pathogenetic mechanisms of oral lipomas are still unclear. They are usually treated by surgical excision and bear excellent prognosis. Here we report a case of intraoral lipoma in 54 year old male patient in the left lower lingual alveolar mucosal region that was treated by surgical excision using electrocautery without any postsurgical complication. One-year follow-up showed no evidence of recurrence.